Regression, Progression and Renewal: The Continuous Redevelopment of Expertise in Police Use of Force Coaching - Staller, Mario S.; Körner, Swen (European journal for security research, 2021)
Professionalism in law enforcement requires the identification and development of expertise of police use of force (PUOF) coaches. Effective PUOF training includes the transfer from the training into the real-world environment of policing. This difference between working in the field and working as a PUOF coach has not been thoroughly investigated. However, research in other professional domains has shown that practical competence in the subject matter itself does not make a coach effective or successful. With this article, we conceptualize expert practice in PUOF instruction on the basis of a conflict management training setting in the security domain. First, by discussing a model of “territories of expertise”, we point out the dynamic and contextual character of expertise within the PUOF domain. Second, by conceptualizing expertise as a process and effect of communication, we provide a framework that describes and examines the interdependency between performance-based and reputation-based expertise. These considerations present two practical challenges, which we recommend professional law enforcement institutions to engage. We close by providing practical orientations and pointers for addressing these issues.